Comprehensive review on improved honey production: techniques, challenges, opportunities, and future prospects in Africa - Tadele, Etsemeskel; Worku, Destaw; Muluneh, Teshager; Ayana, Yitayih; Melese, Abebe (Frontiers in Bee Science, 2025)
Beekeeping production in Africa is important for economic development, food security, environmental conservation, and social well-being. It is important for employment, income generation, plant pollination, ecological awareness, medication, and nutrition. The objective of this review is to explore the improvement of honey production, navigating the causes that reduce honey production as well as techniques to optimize honey production, opportunities, and future prospects in Africa. The improvement of honey production in Africa faces various economic, social, and environmental limits that reduce its production. The causes of low honey production include traditional beekeeping system, inadequate management, technical gaps, and environmental factors as well as lack of technological knowledge, inadequate training, and market constraints, which collectively impede the producers’ ability to improve their honey production. Techniques to improve honey production include improving the beekeeping management system, enhancing forage resources, post-harvest, and value addition, and capacity building and extension services. Improved honey production opportunities include the expansion of beekeeping as an agribusiness, the availability of rich floral diversity to high-quality honey, the adoption of modern beekeeping technologies, resilience to climate change with pollination services, access to both local and export markets, and the incorporation of digital and mobile innovations in beekeeping practices. By strengthening honey production through investment in modern beekeeping practices, enhancing cooperative structures, improving market access, and supporting policy frameworks, stakeholders possess the capacity to collectively transform the honey sector into a sustainable and resilient industry.